How bởi vì you find at equation of the tangent line to the graph displaystyley=fraccosxsinx+2 at x =pi/2?
https://socratic.org/questions/how-do-you-find-at-equation-of-the-tangent-line-to-the-graph-y-cosx-sinx-2-at-x-
displaystyley=fracpi6-frac13x Explanation:Start by finding the y-coordinate of tangency.displaystyley=fraccosleft(fracpi2 ight)sinleft(fracpi2 ight)+2 ...

Bạn đang xem: Cho hàm số y= cosx/1

How vị you determine graphically & analytically whether displaystyley_1=fraccosxsinx is equivalent khổng lồ displaystyley_2=cotx ?
https://socratic.org/questions/how-do-you-determine-graphically-and-analytically-whether-y-1-cosx-sinx-is-equiv
Dean R. Apr 23, 2018 Sincedisplaystylecotx=fraccosxsinxby definition, there's no reason or meaning lớn graphically or analytically verifying this, so I ...
How vị you use the quotient rule khổng lồ find the derivative of displaystyley=frac1+cosleft(x ight)1+sinleft(x ight) ?
https://socratic.org/questions/how-do-you-use-the-quotient-rule-to-find-the-derivative-of-y-1-cos-x-1-sin-x
Psykolord1989 . · Amory W. Sep 9, năm trước The quotient rule states that given functions u and v such thatdisplaystyley=fraculeft(x ight)vleft(x ight),fracleft.dy ight.left.dx ight.=fracu'left(x ight)vleft(x ight)-uleft(x ight)v'left(x ight)v^2left(x ight) ...
How bởi vì you find the exact value displaystyle anleft(x-y ight) if displaystylesinx=frac817,cosy=frac35 ?
The answer isdisplaystyle=-frac3677 Explanation:We use displaystylecos^2x+sin^2x=1displaystylecos^2y+sin^2y=1displaystylesinleft(x-y ight)=sinxcosy-sinycosx ...

Xem thêm: Hàm Đếm Ngày Tháng - Tính Chênh Lệch Giữa Hai Ngày

How bởi you differentiate displaystyley=3xcosleft(fracx3 ight)-sinleft(fracx3 ight) ?
the answer displaystyley'=frac8cosleft(fracx3 ight)3-xsinleft(fracx3 ight) Explanation:show below displaystyley=3xcosleft(fracx3 ight)-sinleft(fracx3 ight) ...
How vày you simplify displaystylefraccosleft(x-y ight)sinleft(x-y ight) to trigonometric functions of x & y?
https://socratic.org/questions/how-do-you-simplify-cos-x-y-sin-x-y-to-trigonometric-functions-of-x-and-y-1
Simplify trig expressionExplanation: displaystylefraccosleft(x-y ight)sinleft(x-y ight) =displaystyle=fraccosx.cosy+sinx.sinysinx.cosy-siny.cosx
Thêm Mục

left< eginarray l l 2 & 3 \ 5 và 4 endarray ight> left< eginarray l l l 2 và 0 & 3 \ -1 và 1 & 5 endarray ight>

EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు